Effect of drip irrigation scheduling and mulching practice on pointed gourd (Trichosanthes dioica Roxb.) pot-cultivation in Patuakhali Bangladesh - Mamun Hossain, S. A. A.; Kayum, M. A.; Wang, L.; Md. Shahin (International Journal of Agricultural Technology, 2021)
Pointed gourd is a tropical vegetable that has been cultivated in the Indian subcontinent which dependent on irrigation for profitable cultivation. Mulching has protected the soil water holding capacity with nutrients could be improved the yield. The effect of irrigation scheduling and mulching application in pointed gourd yield, water use efficiency and fruits physical quality was investigated. The result showed that the highest yield was 45.32 t/ha and lowest was 23.19 t/ha in treatment T6 (D2SM) and T7 (2D1NM) respectively which were significantly influenced by the treatments. In which the highest yield was found to be 44.9 % which greater than the control yield (24.99 t/ha). It showed that the highest irrigation water use efficiency (IWUE) and field water use efficiency (FWUE) was obtained from the treatment of highest yield, which is significantly influenced primarily by mulching application. The result also revealed that the highest individual pointed gourd fruit weight and diameter were obtained 35.50 g and 32.92 mm., respectively in treatment T5 (D2PM) which significantly influenced only by irrigation scheduling. However, the highest fruit length was 9.32 cm in T6 (D2SM) which significantly influenced by irrigation and mulching together. The results concluded that the drip irrigation scheduling and mulching practices could be contributed successfully to optimize the irrigation for improving the pointed gourd yield